Guía práctica para la gestión profesional de proyectos de remodelación o construcción en oficinas regionales de la empresa Gestionadora de Créditos S.A. - Valverde-Chavarría, Willie (Instituto Tecnológico de Costa Rica, 2018)
The projects of remodeling or construction of offices, have a strategic importance for Gestionadora de Créditos (GC), that is why the present investigation shows the need to improve the management of said projects, by means of the proposal of a practical guide, for the professional management of projects within the organization. An adequate justification of the problem is made by reviewing the size and importance of these projects in the organization. Taking into account the above, specific objectives are set to ensure that the proposal has a formal sustenance, through a qualitative research within GC. The research consists of three instruments that are the interview, the questionnaire and the documentary analysis, applied to a population composed of technical personnel and managers. The analysis and results of the research are compared with the best practices in project management worldwide and a "practical guide" is obtained, which takes into account all the proposed areas of knowledge (for example, risks and quality) and the stages of the life cycle of a project in general, so that, the proposed solution contains template and procedures to help the organization in the application in large and small projects. In the end, the present investigation makes a series of conclusions and general recommendations that general management can take into account, to continue with the professional management process of remodeling and construction projects; In addition, the culture and organization that this requires.
Proyecto de Graduación (Maestría en Gerencia de Proyectos) Instituto Tecnológico de Costa Rica, Área Académica de Gerencia de Proyectos, 2018.
Keywords: Construcción; Gestión de proyectos; Cultura; Organización; Administración